The Effect Of Use Of Debit Cards And Electronic Money (E-Money) On Operational Expenditures: Case Study Of Food And Beverage Msmes In Ngaliyan District, Semarang City - Melati Permata Julian; Sri Hariyanti (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research aims to determine the effect of using debit cards and electronic money on operational expenditure (Case Study of Food and Beverage MSMEs in Ngaliyan District, Semarang City). This research is quantitative research. The subjects in this research were Food and Beverage MSMEs in Ngaliyan District, Semarang City with a total of 76 respondents. Data collection techniques use questionnaires. The data analysis technique uses multiple linear regression analysis. Analysis of research data using SPSS Version 25. The results of this research show that there is a significant negative influence of debit cards on the operational expenditure of Food and Beverage MSMEs in Ngaliyan District, Semarang City and a significant positive influence of electronic money (E-Money) on the operational expenditure of Food and Beverage MSMEs in the District Visiting Semarang City.